2018
DOI: 10.2217/fon-2018-0155
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Mir-200 Family Members in Lung Cancer: More Than Tumor Suppressors

Abstract: miRNAs are a class of single-stranded noncoding RNAs, which have no coding potential, but modulate many molecular mechanisms including cancer pathogenesis. miRNAs participate in cell proliferation, differentiation, apoptosis, as well as carcinogenesis or cancer progression, and their involvement in lung cancer has been recently shown. They are suggested to have bidirectional functions on important cancer-related genes so as to enhance or attenuate tumor genesis. Epithelial-mesenchymal transition (EMT) is a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 98 publications
5
34
0
Order By: Relevance
“…2528 MALAT1 and PD-L1 promote NSCLC progression, while multiple miR-200 family members play a role in fighting it. 2936 Consistent with previous reports, we found that MALAT1 and PD-L1 were highly expressed in NSCLC, while miR-200a-3p was significantly downregulated. The starBase and TargetScan suggested that miR-200a-3p has possible binding sites of MALAT1, and PD-L1 was also one of the downstream targets of miR-200a-3p.…”
Section: Discussionsupporting
confidence: 91%
“…2528 MALAT1 and PD-L1 promote NSCLC progression, while multiple miR-200 family members play a role in fighting it. 2936 Consistent with previous reports, we found that MALAT1 and PD-L1 were highly expressed in NSCLC, while miR-200a-3p was significantly downregulated. The starBase and TargetScan suggested that miR-200a-3p has possible binding sites of MALAT1, and PD-L1 was also one of the downstream targets of miR-200a-3p.…”
Section: Discussionsupporting
confidence: 91%
“…The miR-200 family targets the expression of many genes, including ZEBs (Zinc finger E-boxbinding homeobox), which are the transcription factors that regulate cellular transformation, more specifically epithelial-to-mesenchymal transition (EMT), during cancer development and progression through repression of adhesion molecules such as E-cadherin [51]. Members of the miR-200 family also host diagnostic and prognostic potential in other cancer sites such as gastric, ovarian, lung and colorectal cancer [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…40 Recent study also demonstrated that miR-200 family members suppressed the epithelial-mesenchymal transition of lung cancer. 41 The tumor suppressive role of miR-200 family is closely associated with the glinoma initiation, progression and metastasis. 42 These findings suggested the opposite function of miR-200a-3p and other miR-200 family members in cancers.…”
Section: Discussionmentioning
confidence: 99%